2020
DOI: 10.1016/j.annonc.2020.08.651
|View full text |Cite
|
Sign up to set email alerts
|

537MO First-in-human study of JNJ-64619178, a protein arginine methyltransferase 5 (PRMT5) inhibitor, in patients with advanced cancers

Abstract: Background: PRMT5 regulates proteins important for tumorigenesis via symmetric arginine dimethylation (SDMA). JNJ64619178 is an oral, potent and selective PRMT5 inhibitor that demonstrates efficacy in multiple tumor models. Here, we present a phase I study of JNJ64619178 in adults with advanced solid tumors and non-Hodgkin lymphoma (Part 1).Methods: Dose escalation was supported by a modified continual reassessment method. Patients (pts) received JNJ64619178 either intermittently (14 days on/7 days off) or onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Regardless, this targeted treatment will still be the only treatment that encapsulates a substantial subgroup within the PDAC cohort [24]. Furthermore, early phase trials have already demonstrated the safety of this class of drugs [110,111]. Thus, PRMT5 is poised for rapid translation into PDAC treatment once the underlying mechanism is better elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless, this targeted treatment will still be the only treatment that encapsulates a substantial subgroup within the PDAC cohort [24]. Furthermore, early phase trials have already demonstrated the safety of this class of drugs [110,111]. Thus, PRMT5 is poised for rapid translation into PDAC treatment once the underlying mechanism is better elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to phase I trials of PRMT5 inhibitors (GSK3326595 and JNJ64619178) in haematological malignancies and solid cancers. Their respective activities in head and neck squamous cell carcinoma, breast and adenoid cystadenocarcinoma have recently been reported with proven safety [110,111]. Similar trials with PF-06939999 (NCT03854227), PRT811 (NCT04089449) and PRT543 (NCT03886831) are currently ongoing.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…These results led Janssen to advance JNJ64619178 to phase I trials in 2018 for the treatment of relapsed/refractory B cell non-Hodgkin lymphoma or advanced solid tumours (NCT03573310). 268 Thus far, any observed adverse events have been manageable and there has been evidence of clinical activity. Full results are expected to be reported in July 2022.…”
Section: Type I Prmtsmentioning
confidence: 99%
“…By contrast, the e cacy of rst-and second-generation epigenetic drugs in solid tumors has been disappointing. However, recent results obtained with histone methyltransferase Enhancer of Zeste Homolog 2 (EZH2) inhibitors in SMARCB1-defective tumors [12], isocitrate dehydrogenase (IDH1) inhibitors in IDH-mutant cholangiocarcinoma [13] and PRMT5 inhibitors in adenoid cystic carcinoma [14][15][16] have challenged this paradigm, and suggested that, like targeted therapies, epigenetic-modifying drugs should be used in a "precision medicine" approach based on a molecular selection.…”
Section: Introductionmentioning
confidence: 99%